PERBANDINGAN KEBIJAKAN DESENTRALISASI DI BEBERAPA NEGARA ASIA TENGGARA - Supriyatno, Yanto (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2010)
This is a study on development of decentralization politics in some Asian countries, Malaysia, Thailand, the Philippines and Indonesia. It seems that some factors likelocal government, participating of people and non government sector are really needed to develop their regencies or local development